2017
DOI: 10.17652/rpot/2017.4.13877
|View full text |Cite
|
Sign up to set email alerts
|

The occupational stress in International Business Travellers of a multinational of the automotive sector

Abstract: International business travelers constitute an emerging type of international mobility, and there is a gap in terms of studies that address well-being. Based on the Holistic Model of Stress, we intend to explore the occupational stress associated with business travel through a qualitative case study using document analysis and semi-structured interviews. We verified a predominance of distress sources in the trip stage and the adoption of coping strategies focused on the problem. Personal and professional facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Consistent with the JD-R model (Bakker and Demerouti, 2017;Schaufeli and Taris, 2014) prior research has shown that job demands in excess can increase stress and burnout among IBTs (e.g. Cardoso and Jordão, 2017;Connor and Patron, 2008), and a decline in these demands may have a positive impact on health (e.g. Liese et al, 1997), work engagement and well-being (Lirio, 2014;M€ akel€ a et al, 2015b).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 75%
“…Consistent with the JD-R model (Bakker and Demerouti, 2017;Schaufeli and Taris, 2014) prior research has shown that job demands in excess can increase stress and burnout among IBTs (e.g. Cardoso and Jordão, 2017;Connor and Patron, 2008), and a decline in these demands may have a positive impact on health (e.g. Liese et al, 1997), work engagement and well-being (Lirio, 2014;M€ akel€ a et al, 2015b).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 75%
“…A total of 6 mixed method articles were found combining quantitative and qualitative tools ( Dimberg, Mundt, Sulsky, & Liese, 2001 ; Jais et al, 2015a , Jais et al, 2015b ; Roy & Filiatrault, 1998 ; Shortland, 2015 ; Striker et al, 1999 ). Out of the 36 qualitative articles, the majority used interviews, with a few articles combining interviews with some corporate documentation ( Cardoso & Jordão, 2017 ; Haynes, 2010 ; Mayerhofer, Schmidt, Hartmann, & Bendl, 2011 ; Suutari et al, 2013 ) or focus groups ( Pereira, Malik, Howe-Walsh, Munjal, & Hirekhan, 2017 ; Tahvanainen et al, 2005 ). Qualitative studies ranged from 5 to 120 interviewees.…”
Section: Resultsmentioning
confidence: 99%
“…Making use of the IBT option for international deployment requires a good understanding of the particular job characteristic with IBTs being particularly prone to developing physical and psychological illness (Cardoso and Jordão, 2017; Cohen et al , 2017; Mäkelä and Kinnunen, 2018; Rundle et al ., 2018). Research also suggests that working as an IBT often is accompanied by a worsened social life, community and family relationships (Cohen and Gössling, 2015), loneliness and isolation (Gustafson, 2014), work–life balance issues (Niessen et al ., 2018) and degraded quality time at home due to needing to recover and prepare for the next trip (Black and Jamieson, 2007).…”
Section: Introductionmentioning
confidence: 99%